Binding studies of cucurbit[7]uril with gold nanoparticles bearing different surface functionalities. Issue 23 (3rd June 2015) - Yesilbag Tonga, Gulen; Mizuhara, Tsukasa; Saha, Krishnendu; Jiang, Ziwen; Hou, Singyuk; Das, Riddha; Rotello, Vincent M.
Graphical abstract: Abstract: Host–guest interactions between a synthetic receptor, cucurbit[7]uril (CB[7]), and gold nanoparticles (AuNPs) have been quantified using isothermal titration calorimetry. AuNPs were functionalized with ligands containing tertiary or quaternary benzylamine derivatives, with electron donating or withdrawing groups at the para position of the benzene ring. Analysis of binding interactions reveals that functional groups at the para position have no significant effect on binding constant. However, headgroups bearing a permanent positive charge increased the binding of AuNPs to CB[7] ten-fold compared to monomethyl counterparts.